Influence of Dental Pain and Tooth Sensitivity on the Intention to Quit Smoking among Schoolchildren. (9th July 2020) - Nazir, Muhammad; AlAbdullah, Hassan; Alhareky, Muhanad; Al-Ansari, Asim; Alhumaid, Jehan
Abstract : Objective . To evaluate the association between oral health problems and sociodemographic factors with the intention to quit smoking and join the tobacco cessation program among schoolchildren. Materials and Methods . This cross-sectional study included a sample of 10–12 grade male students from public high schools in different cities of the Eastern province of Saudi Arabia. Schoolchildren responded to a pilot-tested questionnaire about self-reported oral health problems and the intention to quit smoking. Bivariate and multivariate logistic regression analyses were performed. Results . Out of 587 schoolchildren, 199 were smokers with a smoking prevalence of 33.9%. Significantly higher proportions of smokers than nonsmokers had tooth sensitivity (P = 0.029) and dryness of the mouth (P = 0.001). Most smokers (75.9%) had a family history of smoking, and 51.8% started smoking within the last two years. Tooth sensitivity (56.3%), dental cavities (52.8%), and dental pain (44.7%) were highly prevalent among smokers. About one-third of smokers expressed their intention to quit smoking (38.2%) and join a smoking cessation program (33.7%). Tooth sensitivity (OR = 3.7, P = 0.004) and dental pain (OR = 2.84, P = 0.014) were significantly associated with quitting smoking. In addition, smokers with tooth sensitivity (OR = 3.22, P = 0.007) had higher odds of joining a smoking cessation program than those without tooth sensitivity. The smokers who started smoking within the last two years (OR = 3.97, P = 0.002) were more likely to quit smoking than those who initiated smoking for more than two years. Conclusion . Oral health problems were highly prevalent among smokers. Tooth sensitivity was significantly associated with quitting smoking and joining a cessation program in children. The awareness about the adverse effects of smoking on oral health should be part of regional, national, and global tobacco prevention policies and programs.